JURNAL GAYA BELAJAR PESERTA DIDIK KELAS XI IPS PADA MATA PELAJARAN GEOGRAFI DI SMAN 8 KOTA PADANG - Nurhidayah, Tiara Parin; Suasti, Yurni (JURNAL BUANA, 2024)
This research was conducted with the aim of identifying the learning styles of students in class XI IPS in Geography subjects at SMAN 8 Padang City. This research is a descriptive quantitative research. The population in this study were students of class XI IPS SMAN 8 Padang which amounted to 121 students. Sampling in this study using random sampling technique, which ultimately resulted in 93 students. While the data collection method is done by observation, questionnaire, and documentation. The results showed that of the 93 students who became the population of this study, the highest number of 51 students 55% were those who had a visual learning style, students who had an auditory learning style were 32 students 34%, and students who had a kinesthetic learning style were many 10 students 11%.